Birds - Doherty, Gillian; Reynolds, S. James (EDC Pub. Tulsa, OK, 2001)
Referring readers to Web sites specially chosen by Usborne editors and web researchers, this book takes a look at some of the amazing powers of birds flight, elaborate courtship displays, and incredible nest-building abilities